Language, identity and culture: a study of language maintenance and shift among Amabhaca raised in Umzimkhulu, KwaZulu Natal - Majola, Yanga Lusanda Praiseworth (My University, 2021)
Umzimkhulu is a small town in KwaZulu-Natal (KZN), previously Bantustan of Transkei. The people in this town speak isiBhaca, a language which is closely related to three Nguni languages (viz. IsiXhosa, IsiZulu and siSwati), but has no official status in South Africa. IsiZulu and isiXhosa are used for official purposes such as education, health, religious and government departments even though the people of Umzimkhulu regard themselves as speakers of isiBhaca and this affects isiBhaca speakers at many levels, the first one being the confusion of having two languages used in different sectors and secondly, having two powerful languages which seem to overpower isiBhaca and this affects the identity of isiBhaca speakers. The primary objectives of the study were to gain an understanding of the importance of language to the cultural identity of amaBhaca and to also discover if isiBhaca is or can be maintained of there is a possible shift towards isiZulu or isiXhosa and to establish the attitudes held by isiBhaca First Language (L1)speaking citizens of Umzimkhulu towards isiBhaca. The study employed a mixed-methods approach. It is useful to consider the full range of responsibilities for data gathering in any study and to organise these methods by their degree of predetermined nature, their use of closed-ended questioning and their focus for numeric versus non-numeric data analysis. Data were gathered from key informants identified as speakers of isiBhaca who were born and bred in Umzimkhulu. The study found that much as isiBhaca is regarded as a dialect of isiXhosa it is linguistically closer to isiZulu than it is to isiXhosa, even though most respondents felt that isiBhaca is a language of its own and the continuous use and empowerment of isiZulu and isiXhosa in Umzimkhulu particularly in the professional settings is detrimental to isiBhaca and this subsequently has the potential of endangering isiBhaca existence and might lead to its attrition. The study further revealed that isiBhaca was mostly used for traditional or informal situations in Umzimkhulu and its speakers mostly had to accommodate speakers of isiZulu and isiXhosa in most cases as these are the standard languages around it, although they were fearful that their cultural identity was in trouble
A thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy: African Languages and Linguistics, in The School of Literature, Language and Media, Faculty of Humanities, University of The Witwatersrand, 2021